Investigation of dynamic responses of skin simulant against fragment impact through experiments and concurrent computational modeling - Pandey, Punit Kumar; Ganpule, S. G. (Frontiers in Bioengineering and Biotechnology, 2024)
Perforation of the skin by the fragment impact is a key determinant of injury severity and incapacitation during modern asymmetric warfare. Computational models validated against experimental data are desired to simulate the response of skin simulant against fragment impact. Towards this end, using experiments and concurrent computational modeling, we have investigated the dynamic response of the skin simulant against fragment impact. Fragment simulating projectiles (FSPs) of 1.10-g and 2.79-g were considered. Response of the skin simulant was investigated in terms of threshold velocity, energy density, peak displacement, and failure mechanisms. Results illustrate numerous salient aspects.Skin simulant failed by cavity shearing followed by the elastic hole enlargement. Results were sensitive to the strain rate. The best agreement between the simulation and the experimental results was achieved when input stress-strain curves to the simulation were based on the full spectrum of strain rates. When a single stress-strain curve corresponding to a specific strain rate was used as an input, threshold velocity and peak displacement of the skin simulant were either underpredicted or overpredicted, depending on the considered strain rate. Threshold velocity was also sensitive to the value of input failure strain; the best agreement with the experiment was obtained when the failure strain was based on the theoretical limiting strain. When the material of the FSP was changed to plastics, the threshold velocities were increased by upto 33%. However, energy densities and generated stresses exceeded the contusion and laceration thresholds for the skin.